The Activators of Cyclin-Dependent Kinase 5 p35 and p39 Are Essential for Oligodendrocyte Maturation, Process Formation, and Myelination - Luo, Fucheng (J Neurosci, 2016)
The regulation of oligodendrocyte development and myelin formation in the CNS is poorly defined. Multiple signals influence the rate and extent of CNS myelination, including the noncanonical cyclin-dependent kinase 5 (Cdk5) whose functions are regulated by its activators p35 and p39. Here we show that selective loss of either p35 or p39 perturbed specific aspects of oligodendrocyte development, whereas loss of both p35 and p39 completely inhibited the development of mature oligodendrocytes and myelination. In the absence of p35, oligodendrocyte differentiation was delayed, process outgrowth was truncated in vitro, and the patterning and extent of myelination were perturbed in the CNS of p35(−/−) mice. In the absence of p39, oligodendrocyte maturation was transiently affected both in vitro and in vivo. However, loss of both p35 and p39 in oligodendrocyte lineage cells completely inhibited oligodendrocyte progenitor cell differentiation and myelination both in vitro and after transplantation into shiverer slice cultures. Loss of p35 and p39 had a more profound effect on oligodendrocyte development than simply the loss of Cdk5 and could not be rescued by Cdk5 overexpression. These data suggest p35 and p39 have specific and overlapping roles in oligodendrocyte development, some of which may be independent of Cdk5 activation. SIGNIFICANCE STATEMENT The development of oligodendrocytes and myelination is essential for normal CNS function and cyclin-dependent kinase 5 (Cdk5) activity is critical for oligodendrocyte maturation, but how Cdk5 activity is controlled is unclear. Here we show that the coactivators of Cdk5, p35 and p39, regulate distinct stages of oligodendrocyte development and myelination. Loss of p35 perturbs oligodendrocyte progenitor cell differentiation, whereas loss of p39 delays oligodendrocyte maturation. Loss of both completely inhibits oligodendrogenesis and myelination. Disruption of oligodendrocyte development was more pronounced in p35(−/−);p39 shRNA cells than loss of Cdk5 alone and could not be rescued by Cdk5 overexpression, suggesting that p35 and p39 have Cdk5-independent roles during oligodendrocyte development. These studies provide novel targets for therapeutic intervention in conditions in which myelination is perturbed.